To Hegra through al-Qusayr. The al-'Ula-al-Wajh Survey Project - Zbigniew T. Fiema (Polish Archaeology in the Mediterranean, 2020)
The al-‘Ulā–al-Wajh Survey Project deals with ancient trade routes between al-‘Ulā and Madā’in ‘Ṣāliḥ (ancient Hegra) and the Red Sea in the area of al-Wajh in northwestern Saudi Arabia. This investigation is related to economics of longdistance maritime and caravan trade and the utilization of the "Incense Route" which served to convey frankincense and other commodities from South Arabia to the Mediterranean during the Hellenistic and Roman periods. The Project is also concerned with the localization of Nabataean seaports on the Red Sea coast, such as Leuke Kome and Egra Kome. The results of two fieldwork seasons are presented including a potential caravan route to Hegra along the Wādī al-Hamd. The site of Nabataean al-Qusayr is highlighted here as the finds from there indicate a participation in the long-distance trade between the Mediterranean, Egypt and the Red Sea region.